Respuesta :
Jessica solved for the correct value of a, but Sally's review was incorrect.
Answer:
Jessica’s work is correct and Sally’s review is incorrect
Step-by-step explanation:
I'm just assume it's a vertical parabola
we know that
The equation of a vertical parabola in vertex for is equal to
[tex]y=a(x-h)^{2}+k[/tex]
where
(h,k) is the vertex
In this problem we have
[tex](h,k)=(6,-3)[/tex]
point [tex](8,-11)[/tex]
substitute
[tex]-11=a(8-6)^{2}-3[/tex]
[tex]-11=a(2)^{2}-3[/tex]
[tex]-11=4a-3[/tex]
[tex]-8=4a[/tex]
[tex]a=-2[/tex]
To find the equation using the value of a and the vertex point
so
[tex]y=-2(x-6)^{2}-3[/tex]
therefore
Jessica’s work is correct and Sally’s review is incorrect